2021
DOI: 10.1155/2021/6203759
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immune-Related Risk Signatures for the Prognostic Prediction in Oral Squamous Cell Carcinoma

Abstract: Background. Oral squamous cell carcinoma (OSCC) is the most common type of oral cancer, which remains a major cause of morbidity and mortality in patients with head and neck cancers. However, the critical immune-related signatures and their prognostic values have rarely been investigated. Materials and Methods. Gene differential analysis was used to measure the differences of gene expression between the groups. Correlation analysis was used to assess the association between the gene expression levels and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Our study has many highlights. Several researches previously have proposed certain risk signatures based on various characteristics, in hopes of stratifying the prognosis of cancer patients 53,54 . Zheng et al have identified a signature of seven‐lncRNA to predict the OS of patients with AML 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has many highlights. Several researches previously have proposed certain risk signatures based on various characteristics, in hopes of stratifying the prognosis of cancer patients 53,54 . Zheng et al have identified a signature of seven‐lncRNA to predict the OS of patients with AML 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Several researches previously have proposed certain risk signatures based on various characteristics, in hopes of stratifying the prognosis of cancer patients. 53 , 54 Zheng et al have identified a signature of seven‐lncRNA to predict the OS of patients with AML. 6 Compared with those studies, the WGCNA used in our study has a unique advantage in dealing with gene expression data because it allows us to gain insight into the connection between coexpression modules and clinical characteristics of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CTSG is associated with tumor angiogenesis and metastasis, participating in host defense and neutrophil-related immune responses, and serving as a target of immunotherapy for acute myeloid leukemia (AML) ( 38 ). CTSG is also closely related to the survival of several cancer types, including soft tissue sarcoma, muscular invasive bladder cancer, and lymph node-negative breast cancer ( 39 ), and is a potential immune-related biomarker for OSCC ( 40 ). The current study showed that CTSG could inhibit the proliferation, migration, invasion, and colony formation of SCC15 cells in vitro , confirming that CTSG plays a key role in tumorigenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Gormley et al 25 showed that CTSS could be a diagnostic marker for CRC and may increase 5-Fu and folic acid therapeutic sensitivity. Many studies have indicated that CTSG, a member of the Cathepsin family, functions as a cancer suppressor in many tumors, inhibiting the malignant features and cancers development, like breast, bladder, oral squamous cell cancer, and acute myeloid leukemia 26 - 29 . However, CTSG role in CRC oncogenesis has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%